STUDI KOMPARATIF DISTRIBUSI PENDAPATAN MASYARAKAT SEKITAR TAMBANG SEBELUM DAN SESUDAH MENDAPATKAN PROGRAM CORPORATE SOCIAL RESPONSIBILITY DI KABUPATEN BERAU - La Ode Ilyas (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2013)
Comparative study of the distribution of income communities around the mine before and after the Corporate Social Responsibility program in Berau is a study that aims to compare income communities around the mine before and after receiving the Corporate Social Responsibility ( CSR ) in Berau well as knowing the distribution of income communities. Based methods, this kind of research, including survey research combined with evaluation studies, because these studies can be conducted on large populations and small, and the data is the data sample studied samples taken from the population. In this study will be found relative events and distribution as well as the relationships between variables. Researchers can conclude that CSR programs are very influential on increasing revenue where t > t table then Ho is rejected and Ha accepted. Then it can be said that there are differences in income communities around the mine before and after getting the CSR program in Berau.